Pelatihan Pembuatan Buket Jajanan Dalam Menciptakan Minat Wirausaha Pada Siswa/I SMP IT Darul Hikmah Desa Harapan Baru Kecamatan Sei Lepan Kabupaten Langkat - Enda Lovita Pandiangan; Kamaliah; Rizki Pratama; Dwi Marlina; Sintya Putri; Murni Agustina; Sri Mulyani; Putri Ardia Pramesti (Fusion: Jurnal Pengabdian kepada Masyarakat, 2023)
Entrepreneurship is one way for someone to work and pursue a career for their life in the future. Entrepreneurship can also open new jobs for people who need or are looking for a job, besides that it can help the government's task of reducing unemployment growth in this country. In this modern era, it's not only adults or old people who dare to start their businesses, now there are many young people who have the courage to take steps to start their businesses and not a few who can achieve success at a young age. We see a lot around us of efforts that were pioneered by young people who are still pursuing their education. Whether it's a food business, fashion, motivator and so on.